Rationale of a comparative analytical study on matrix metalloproteinases associated with genital prolapse in Congolese women from the town of Kananga in the Democratic Republic of Congo: research protocol - Kayembe, Antoine Tshimbundu; Muela, Andy Mbangama; Tozin, Rahma Raschid (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Genital prolapse is a pelvic static disorder associated with urinary, digestive and genital disorders which bother the patient. The fear of these discomforts has pushed many Western countries to adopt beneficial preventive measures for women at risk, notably the administration of estrogen-progestogens and the prevention of obstetric trauma. These two preventive factors play an inhibitory role on matrix metalloproteinases degrading the collagens which ensure ligament firmness. This link between matrix metalloproteinases and collagen is implicated by many researchers in the occurrence of genital prolapse. Objectives are to determine the epidemiological and clinical profile of genital prolapse, to identify the non-molecular factors associated with it, to determine the level of matrix metalloproteinases-1, -2 and -9 in non-prolapsed and prolapsed pelvic tissues, and to identify the types MMPs associated with genital prolapse in Congolese women from the town of Kananga in central Kasai in DR Congo. Methods: We designed a protocol for a comparative analytical study focusing on the epidemiology and the level of matrix metalloproteinases in non-prolapsed and prolapsed pelvic tissues in the Bon-Berger and Saint Georges hospitals in the city of Kananga. Women over 40 years of age and of any parity suffering from genital prolapse and other benign gynecological pathologies requiring hysterectomy will be included in the study according to non-probabilistic convenience sampling. Conclusions: This study will evaluate the level of matrix metalloproteinases-1, -2 and -9 in prolapsed tissues and identify the type of matrix metalloproteinases most associated with genital prolapse in our setting.